The what, why and when of adapting interventions for new contexts: A qualitative study of researchers, funders, journal editors and practitioners' understandings. - Lauren Copeland; Hannah Littlecott; Danielle Couturiaux; Pat Hoddinott; Jeremy Segrott; Simon Murphy; Graham Moore; Rhiannon Evans (PLoS ONE)
Background The adaptation of interventions for new contexts is a rapidly developing research area. To date there is no consensus-based guidance to support decision-making and recommend adaptation processes. The ADAPT study is developing such guidance. This aim of the qualitative component of the study was to explore stakeholders' understandings of adaptation, as to date there has limited consideration of how different concepts and meanings shape decision-making and practice. Methods A case study research design was used. Participants/cases were purposefully sampled based on study outcome, study design, expertise, context and country. Semi-structured interviews were conducted with a sample of researchers (n = 23); representatives from research funding panels (n = 6); journal editors (n = 5) and practitioners (n = 3). Data were analysed using the Framework approach. Overarching themes were discussed with the ADAPT study team, with further iterative refinement of subthemes. Results The results generated four central themes. Four themes related to stakeholders' understanding: 1) definitions of adaptation and related concepts; 2) rationales for undertaking adaptation; 3) the appropriate timing for adaptation; and 4) ensuring fidelity when implementing adapted interventions. Conclusion The findings highlight the lack of clarity around key concepts and uncertainty about central decision-making processes, notably why interventions should be adapted, when and to what extent. This has informed the ADAPT study's guidance, shaping the scope and nature of recommendations to be included and surfacing key uncertainties that require future consideration.